The Consequences of Globalisation : India's Software Industry and Cross-Border Labour Mobility - Commander, Simon; Chanda, Rupa; Kangasniemi, Mari; Winters, L. Alan (2012)
The Indian software industry is a prime example of globalisation. The industry has been characterised by large cross-border mobility of its skilled labour force. Using a unique survey of Indian software firms, our paper quantifies the extent and impact of mobility on firm behaviour and performance. Cross-border labour mobility in the paper refers to both temporary and permanent labour flows by Indian software professionals. The picture that emerges is of a highly mobile world in which temporary mobility has been an important characteristic of the industry. A significant number of workers have work experience abroad in a developed country. Moreover, the share of skilled workers with such experience has been positively associated with the incidence of skilled migration from the firm. This suggests network effects are at work. In terms of the impact on performance--as measured by the change in turnover per worker and the change in the employment size of the firm--the paper finds little evidence of a robust adverse effect. Further, the evidence suggests that there have been important external effects at work, as through changes in the willingness of workers to acquire skills, as well as through increased provision of educational services. These have further abated the risk of a brain drain. However, the software industry may be rather different from other industries. Our results need to be interpreted as the outcome of a particular case of skilled migration and not one necessarily representative of all types of skilled migration and source sectors.